MOTIF PENDENGAR DALAM MENDENGARKAN RADIO VIRGIN JAKARTA - Atika, Mega Marta; van Eymeren, Margaretha Margawati (Eko dan Bisnis: Riau Economic and Business Review, 2019)
Radio an example of mass communication. Radio Virgin started 2015. and is owned by MPG Media by franchise with Radio Virgin International. Radio Virgin gained 140,000 listeners in its three months. This research was conducted to find out what is the listener's motive in listening to Radio Virgin. The researcher uses Uses & Gratification theory with four motive indicators in this research, which we information motive, personal identity motive, interaction motive and social integration, and entertainment motive. The method used is qualitative research. The method that will be used in this research is in-depth interviews with five resource persons in accordance with the research criteria. The results showed the research of motive information and entertainment motives. The results showed the discovery of motive information and entertainment motives. Motive information found in this study, the information motive will be music concerts that will be held in Indonesia and overseas, and information about the news music offered by Radio Virgin. While the main motive of entertainment found in this study is mRadio Virgin provides the latest songs with different formats and concepts, so informants feel their needs we fulfilled in terms of entertainment